If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 40 = 6x + -60 Reorder the terms: 40 + -5x = 6x + -60 Reorder the terms: 40 + -5x = -60 + 6x Solving 40 + -5x = -60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 40 + -5x + -6x = -60 + 6x + -6x Combine like terms: -5x + -6x = -11x 40 + -11x = -60 + 6x + -6x Combine like terms: 6x + -6x = 0 40 + -11x = -60 + 0 40 + -11x = -60 Add '-40' to each side of the equation. 40 + -40 + -11x = -60 + -40 Combine like terms: 40 + -40 = 0 0 + -11x = -60 + -40 -11x = -60 + -40 Combine like terms: -60 + -40 = -100 -11x = -100 Divide each side by '-11'. x = 9.090909091 Simplifying x = 9.090909091
| 2(10)=24-2(10) | | -4=4v | | 88=x+x-6 | | -x=-77 | | X+2x-5=0 | | 10=24-2(10) | | 3f=-3+12 | | x+x-6=88 | | 400=0.14+2 | | x-6+x=88 | | 6x/3+7/15x+3 | | (x-8)/(-x+77)=2 | | 5(x+3)=-5 | | y=42+-5y | | -1.14*23.25+47= | | y=0.63(0.5)x | | 3/8x-8=-7 | | -.71*23.25+37= | | 8x^3=(-64) | | =(n-5)(2n+4) | | 3(x-2)+(x-12)/6-2*(x+3)/(6)=x/2 | | 20+4k=228 | | 3x=4+x+16 | | 72-5x=8x+16 | | 8x-6=4x+14 | | r/7=-9/7 | | (3x+5)(2x-3)=-5 | | 6x+8=4x-2 | | m/15=-11/15 | | 12=-3(-6x-3) | | x^4+x^3+x^2+3x-6=0 | | z^4+z^3+z^2+3z-6=0 |